SOSIALISASI METODE PEMANTAUAN MAKANAN PENDAMPING ASI (MPASI) ANAK USIA 6-23 BULAN DESA WAGE SIDOARJO - Sa'bania Hari Raharjeng; Pratiwi Hariyani Putri; Anugrah Linda Mutiarani; Ira Dwijayanti; Mery Susantri (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
Provision of appropriate complementary foods (MPASI) is essential to meet children's nutritional needs. There are several indicators for conveying opinions regarding the provision of MPASI, one of which is related to the variety of food ingredients in MPASI. Monitoring is needed to ensure that the MPASI provided is in accordance with recommendations. The purpose of this activity is to improve the knowledge and abilities of Posyandu cadres in monitoring the provision of MPASI using the 1x24 hour Recall method. The methods used are lectures and role-playing practices. The increase in cadre knowledge is measured by pre-post tests. The activity was attended by 40 Posyandu cadres and village midwives. The results of the activity were that overall the cadres experienced an increase in knowledge and were able to apply the 1x24 hour recall method in the implementation of MPASI presentation screenings in terms of food diversity